RANCANG BANGUN MESIN PENCACAH ES BATU DENGAN POSISI MATA PISAU DIAGONAL - Sumardiyanto, Didit; Endah Susilowati, Sri; Seno Septyantoro, Kukuh (Fakultas Teknik dan Teknologi - TANRI ABENG UNIVERSITY, 2025)
Fish is one of the fishery products which has a very high source of protein. Fish is a commodity that rots easily, so it requires extra careful handling in an effort to maintain its quality after being removed from fresh water and sea water. One way to preserve it is to store it in chopped ice. In connection with the need for chopped ice in large quantities, a block ice chopping machine with a diagonal blade position was made. The size of the ice cube chopper machine is 1700mm long, 450mm wide and 1200mm high. The machine uses a drive motor with a power of 1 hp. The production capacity of the machine is. In the first study, the force produced by the knife was 7.90 kg/minute